Konsep Learning Community Dalam Merdeka Belajar Menurut Al-Qur’an Surat Al-Kahfi Ayat 10-15 Kajian Ilmu Pendidikan Islam - Wahidah, Evita Yuliatul; Hidayati, Ismah (MASAGI : Jurnal Pendidikan Agama Islam, 2024)
In the pursuit of cultivating quality human beings, education plays an indispensable role. As beings endowed with immense potential by Allah SWT, it is our duty to continually evolve with the times while adhering to Islamic values. This principle applies to the continuous development and innovation in education and learning processes. An example of such educational advancement, which is either about to be implemented or already practiced in some schools and higher education institutions in Indonesia, is the "Merdeka Belajar" (Freedom to Learn) initiative. Teachers play a crucial role as the key to the success and achievement of students in the learning process, and their effectiveness must be continually enhanced. One of the solutions provided by "Merdeka Belajar" to address educational challenges is through the concept of the Learning Community.   The purpose of this research is to understand the concept of Learning Community within the framework of "Merdeka Belajar" as outlined in the Quran, specifically in Surah Al-Kahfi, verses 10-15, and to explore this concept from the perspective of Islamic Education Studies. The research methodology employed is qualitative library research, which involves a thorough review of related data from both primary and secondary sources to compile and analyze relevant information.   The findings reveal that the concept of Learning Community in "Merdeka Belajar," as depicted in Surah Al-Kahfi verses 10-15, underscores the necessity for humans to engage in continuous learning, drawing from the experiences and knowledge of others. This concept is grounded in the story of the Ashabul Kahfi, illustrating that every individual has equal rights and opportunities to gain education and experience. It emphasizes the importance of healthy discussions and communication among individuals, relying on Allah SWT to achieve a common goal. Keywords : Learning Community, Merdeka Belajar, Ashabul Kahfi